Fluorescence-guided minimally invasive parathyroidectomy: a novel surgical therapy for secondary hyperparathyroidism - Proßt, Rüdiger Lothar; Gahlen, Johannes; Schnülle, Peter; Post, Stefan; Willeke, Frank (American journal of kidney diseases, 2006)
Secondary hyperparathyroidism (SHPT) is a severe and frequent complication in patients with advanced chronic kidney disease, characterized by hyperplasia of all parathyroid glands and elevated serum parathyroid hormone levels. When surgery is required to prevent cardiovascular consequences, bone pain, osteoporosis, or even soft-tissue calcifications, detection of the enlarged glands often can be difficult because of their variability in number and location. A novel surgical technique, fluorescence-guided minimally invasive parathyroidectomy, may facilitate intraoperative localization of parathyroid glands. A 52-year-old woman with SHPT underwent minimally invasive videoscopic-assisted parathyroidectomy after photosensitization with aminolevulinic acid (ALA): Under special fluorescence illumination by D-Light (Karl Storz Co, Tuttlingen, Germany), bilateral neck exploration was performed. All enlarged parathyroid glands were identified because of their ALA-induced intense red fluorescence. Such surrounding structures as thyroid, lymph nodes, and soft tissue remained nonfluorescent and could be distinguished easily from parathyroid glands. Total parathyroidectomy with autotransplantation into the sternocleidoid muscle was performed. In patients with SHPT, exploration of all parathyroid glands during surgery is mandatory. However, to date, there is no convincing technical aid for the surgeon to facilitate this procedure. The ALA-induced fluorescence technique represents an innovative visual detection method for intraoperative identification of parathyroid glands. The technique serves as an additional tool requiring only moderate technical and clinical expenditure.